Home » Blog » Solve the differential equation y′ – 3y = e2x for given initial values

Solve the differential equation y′ – 3y = e2x for given initial values

Solve the following differential equation:

    \[ y' - 3y = e^{2x} \qquad \text{on} \quad (-\infty, +\infty) \]

with y =0 when x =0.


From Theorem 8.3 (page 310 of Apostol) we know that a differential equation of the form

    \[ y' + P(x)y = Q(x), \qquad \text{with} \quad f(a) = b, \]

on an interval I has solution given by

    \[ f(x) = be^{-A(x)} + e^{-A(x)} \int_a^x Q(t)e^{A(t)} \, dt \]

where

    \[ A(x) = \int_a^x P(t) \, dt. \]

In this particular case we apply the theorem with

    \[ P(x) = -3, \qquad Q(x) = e^{2x}, \qquad a = b= 0. \]

This gives us

    \[ A(x) = \int_0^x -3 \, dt = -3x. \]

Therefore,

    \begin{align*}  f(x) &= be^{-A(x)} + e^{-A(x)} \int_a^x Q(t)e^{A(t)} \, dt \\[9pt]  &= e^{3x} \int_0^x e^{-t} \, dt \\[9pt]  &= e^{3x} (-e^{-x} + 1) \\[9pt]  &= e^{3x} - e^{2x}. \end{align*}

Point out an error, ask a question, offer an alternative solution (to use Latex type [latexpage] at the top of your comment):